Comparing and using prominent social accountability frameworks in medical education: Moving from theory to implementation in Northern Ontario, Canada - Wood, Brianne; Bohonis, Hafsa; Ross, Brian; Cameron, Erin (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2022)
Background: Social accountability in medical education is conceptualized as a responsibility to respond to the needs of local populations and demonstrate the impact of these activities. The objective of this study was to rigorously examine and compare social accountability theories, models, and frameworks to identify a theory-informed structure to understand and evaluate the impacts of medical education in Northern Ontario.Methods: Using a narrative review methodology, prominent social accountability theories, models, and frameworks were identified. The research team extracted important constructs and relationships from the selected frameworks. The Theory Comparison and Selection Tool was used to compare the frameworks for fit and relevance.Results: Eleven theories, models, and frameworks were identified for in-depth analysis and comparison. Two realist frameworks that considered community relationships in medical education and social accountability in health services received the highest scores. Frameworks focused on learning health systems, evaluating institutional social accountability, and implementing evidence-based practices also scored highly.Conclusion: We used a systematic theory selection process to describe and compare social accountability constructs and frameworks to inform the development of a social accountability impact framework for the Northern Ontario School of Medicine. The research team examined important constructs, relationships, and outcomes, to select a framework that fits the aims of a specific project. Additional engagement will help determine how to combine, adapt and implement framework components to use in a Northern Ontario framework.